ANALISIS DAYA SAING TENAGA KESEHATAN DALAM ERA MASYARAKAT EKONOMI ASEAN (MEA) DI KOTA KENDARI - Rosnawintang Rosnawintang (JEP (Jurnal Ekonomi Pembangunan), 2015)
The purpose of this study was to determine the competitiveness of health personnel (medical and nursing) in the era of the ASEAN Economic Community (AEC). The type of data in this research is secondary data. Variable competitiveness of health workers is measured by levels of formal education and vocational training based on competency, standardization of professions and certificates of competence. Analysis of the data used is descriptive analysis. The results showed that medical personnel in Kendari competitiveness based on formal education by 100%, competency-based job training amounted to 72.02%, the standardization aspects of the profession amounted to 99.72% and competency certification of 100%. While nurses in Kendari have competitiveness in the era of the MEA is based on a competency-based job training amounted to 42.12%. Competitiveness is a nurse by profession and a certificate of competency standardization amounted to 78.00% and that do not have competitiveness by standardizing the profession and competency certificates amounted to 22.00%.